Preparação dos pretendentes e da criança institucionalizada para adoção: o início do processa de filiação. - Menezes, Karla Fabiana Figueiredo Luna de (2019)
This thesis aimed to analyze how the practice of preparing applicants for adoption and the institutionalized child to join the adoptive family, in the cities of Recife and Olinda, as well as proposing subsidies to think about ways of intervention in the preparation of these applicants. institutionalized child for adoption, considering their demands and particularities. It is a field research, qualitative in nature and was carried out in two moments. In the first, data collection was performed at the Olinda and Recife Childhood and Youth Courts, with two distinct groups of adoption applicants. In the second moment, to analyze the preparation of the child/teenager, we visited two Foster Homes where we interviewed six members of the multiprofessional technical teams (psychologists, social workers and educators), responsible for assisting and subsidizing judicial decisions from the perspective of guaranteeing the rights of the child and teenager. As a data collection instrument in the preparation of the applicants, the field diary was used; to collect data in the preparation of the child/teenager, a semi-structured interview was used. The treatment of the collected information was made by the technique of the Content Analysis and interpreted in the light of the psychoanalytical theory. The research allowed us to realize that the meetings in the Courts are educational, informative and more accessible to the conscious dimension. Although they produce elaboration effects, they are not sufficient to account for the subjective aspects of the applicants, that is, the complexity of the desire. Regarding the preparation of the child / adolescent, the results obtained indicate that there are differences between the practices performed by the teams of the Foster Homes, even differing within the same team; thus, there is no systematization. We conclude from this study that no preparation process or work methodology is capable of guaranteeing the mutual psychic adoption in the relations of filiation and parentalization. However, careful work in this direction minimizes the risk of failure of the foster project and devolution, and facilitates bond building as it offers the opportunity to elaborate.